2011
DOI: 10.4111/kju.2011.52.6.421
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Pyelonephritis: A Retrospective Review of 16 Cases

Abstract: PurposeXanthogranulomatous pyelonephritis is an uncommon disorder of unknown etiology that is characterized by extensive destruction of the involved kidney. It is being increasingly recognized as an important cause of renal morbidity around the world.Materials and MethodsThis retrospective study was undertaken to review the xanthogranulomatous pyelonephritis cases presented at our tertiary care referral center in Bangalore, India.ResultsA total of 16 biopsy-proven cases of xanthogranulomatous pyelonephritis fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 18 publications
1
48
1
2
Order By: Relevance
“…Globally the incidence of xanthogranulomatous pyelonephritis is 0.6 to 1% with female preponderance [13] , but in our study 5 cases have been reported which is found to be discordance with the other study.…”
Section: Discussioncontrasting
confidence: 96%
“…Globally the incidence of xanthogranulomatous pyelonephritis is 0.6 to 1% with female preponderance [13] , but in our study 5 cases have been reported which is found to be discordance with the other study.…”
Section: Discussioncontrasting
confidence: 96%
“…This theory is supported by the observation that urinary tract calculi are present in 70–79% of patients with XGP [2]. XGP accounts for approximately 1% of pyelonephritis cases reported worldwide [3]. …”
Section: Discussionmentioning
confidence: 91%
“…29 The primary presenting symptom is abdominal/ flank pain, followed by fever, dysuria, and weight loss. 30,31 Unilateral lesions are most common, with equal frequency associated with the right and left kidneys. 30 XGP results in either poor renal function or completely nonfunctioning, enlarged kidneys.…”
Section: Xanthogranulomatous Pyelonephritismentioning
confidence: 98%
“…30,31 Unilateral lesions are most common, with equal frequency associated with the right and left kidneys. 30 XGP results in either poor renal function or completely nonfunctioning, enlarged kidneys. 32 Identification on MR imaging revolves again around discovery of a large "staghorn" calculus appearing as a hypointensity (signal-intensity void) 33 in combination with focal atrophy of the surrounding kidney.…”
Section: Xanthogranulomatous Pyelonephritismentioning
confidence: 98%